Molecular Determinants of Modulation of Ca(V)2.1 Channels by Visinin-like Protein 2 - Nanou, Evanthia (American Society for Biochemistry and Molecular Biology, 2012)
Ca(V)2.1 channels, which conduct P/Q-type Ca(2+) currents, initiate synaptic transmission at most synapses in the central nervous system. Ca(2+)/calmodulin-dependent facilitation and inactivation of these channels contributes to short-term facilitation and depression of synaptic transmission, respectively. Other calcium sensor proteins displace calmodulin (CaM) from its binding site, differentially regulate Ca(V)2.1 channels, and contribute to the diversity of short-term synaptic plasticity. The neuronal calcium sensor protein visinin-like protein 2 (VILIP-2) inhibits inactivation and enhances facilitation of Ca(V)2.1 channels. Here we examine the molecular determinants for differential regulation of Ca(V)2.1 channels by VILIP-2 and CaM by construction and functional analysis of chimeras in which the functional domains of VILIP-2 are substituted in CaM. Our results show that the N-terminal domain, including its myristoylation site, the central α-helix, and the C-terminal lobe containing EF-hands 3 and 4 of VILIP-2 are sufficient to transfer its regulatory properties to CaM. This regulation by VILIP-2 requires binding to the IQ-like domain of Ca(V)2.1 channels. Our results identify the essential molecular determinants of differential regulation of Ca(V)2.1 channels by VILIP-2 and define the molecular code that these proteins use to control short-term synaptic plasticity.